Efektifitas Mindfulness Based Stress Reduction (MBSR) terhadap penurunan burnout - nina alfa rizkana (TERAPUTIK: Jurnal Bimbingan dan Konseling, 2023)
Burnout syndrome has a negative impact   and has serious consequences for occupational health.  Various forms of interventions are also carried out to deal with these conditions, both as preventive efforts and reducing the negative impact of burnout.  Several studies have found that mindfulness-based interventions including MBSR are effective in reducing burnout rates.  That's why this literature study was conducted. Aseries aimed to look at the efficacy of MBSR-based interventions. 12 articles were selected based on PRISMA guidelines and the results stated that mindfulness decreased levels of emotional exhaustion and depersonalization, also increased personal accomplishment.